2009
DOI: 10.3155/1047-3289.59.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Mercury Vapor Release from Broken Fluorescent Lamps during Shipping

Abstract: Fluorescent lamps are estimated to annually release 1 t of mercury into the air in the United States; transport of used lamps may play an important role in these emissions. In 1999, the U.S. Environmental Protection Agency added lamps to the universal waste rule to encourage recycling by allowing shipment to recycling facilities by common carrier. The rules required that lamp packaging must be structurally sound and adequate to prevent breakage but did not address vapor release. In 2005, a requirement was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The major reaction products identified were HgI 2 , HgO and HgIO or HgOI. Glenz and coworkers 33 investigated the appropriateness of packing materials in preventing the release of mercury vapour from broken fluorescent lamps. They concluded that a double-boxed package incorporating a laminated foil bag was required to prevent fugitive emissions.…”
Section: Icp-ms As An Elemental Detector As Part Of a Hyphenated Analmentioning
confidence: 99%
“…The major reaction products identified were HgI 2 , HgO and HgIO or HgOI. Glenz and coworkers 33 investigated the appropriateness of packing materials in preventing the release of mercury vapour from broken fluorescent lamps. They concluded that a double-boxed package incorporating a laminated foil bag was required to prevent fugitive emissions.…”
Section: Icp-ms As An Elemental Detector As Part Of a Hyphenated Analmentioning
confidence: 99%
“…In comparison, LEDs have increasingly become the more preferred option because they are more energy-efficient and cost-efficient with a longer lifespan. , Additionally, the LED bulbs are easier to dispose because they do not contain hazardous mercury that is present in the fluorescent lighting system, which would be harmful to the environment . LEDs manufactured for use in indoor farming systems are typically embedded in a panel, together with the required electronics to facilitate their use as lighting systems.…”
Section: Introductionmentioning
confidence: 99%
“…2,12 Additionally, the LED bulbs are easier to dispose because they do not contain hazardous mercury that is present in the fluorescent lighting system, which would be harmful to the environment. 10 LEDs manufactured for use in indoor farming systems are typically embedded in a panel, together with the required electronics to facilitate their use as lighting systems. A layer of encapsulate is usually overlaid over the LED diodes to protect them from mechanical damage and the environment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, various efforts have focused on managing the mercury vapor released from broken CFLs. 7,8 Life cycle analyses have been performed (i) to evaluate the amount of mercury reduced by replacing an incandescent with a CFL bulb, 9 and (ii) to quantify and compare energy and environmental impacts in the life cycle stages of incandescent, CFL, and LED bulbs. 10,11 These LCAs highlighted high impact potentials from energy consumption: for instance, compared to the incandescent bulb on an equivalent quantity basis, the CFLs and LEDs reduced primary energy demand and global warming, human toxicity, and resource depletion potentials by approximately 80% during the use and manufacturing stages.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to the importance of lighting to society, previous studies have investigated various environmental impacts from incandescent, CFL, and LED bulbs. For example, various efforts have focused on managing the mercury vapor released from broken CFLs. , Life cycle analyses have been performed (i) to evaluate the amount of mercury reduced by replacing an incandescent with a CFL bulb, and (ii) to quantify and compare energy and environmental impacts in the life cycle stages of incandescent, CFL, and LED bulbs. , These LCAs highlighted high impact potentials from energy consumption: for instance, compared to the incandescent bulb on an equivalent quantity basis, the CFLs and LEDs reduced primary energy demand and global warming, human toxicity, and resource depletion potentials by approximately 80% during the use and manufacturing stages . We recently published an LED study that addressed the potential environmental impacts derived from the metals in LED “pin-type diodes” with various light intensities and colors .…”
Section: Introductionmentioning
confidence: 99%